Two new species of the water scavenger beetle genus Hemiosus Sharp Coleoptera: Hydrophilidae) from Colombian Andes - González-Rodríguez, Liza M.; García-Hernández, Andrea L.; Clarkson, Bruno (Zootaxa, 2019)
Two new species of Hemiosus (Coleoptera: Hydrophilidae) from the central cordillera of the Colombian Andes are described. Hemiosus molanoi González-Rodríguez & García-Hernández sp. nov. and H. quindiensis González-Rodríguez & Clarkson sp. nov. are described based in 56 adult specimens collected in river-associated sandy puddles (26 specimens of H. molanoi sp. nov.) and temporary puddles near crops (26 specimens of H. quindiensis sp. nov.). Both species are identified mainly by characteristics of the aedeagus: Hemiosus molanoi sp. nov. has subtriangular parameres, median lobe shorter than parameres and longer than appendices which are acuminate and phallobase shorter than parameres, strongly asymmetrical in basal two-fifths; H. quindiensis sp. nov. has parameres gradually tapering towards rounded apices, median lobe shorter than parameres and longer than appendices which are acuminate and phallobase shorter than parameres, strongly asymmetrical in basal half. Dorsal coloration pattern, overall shape of the meso- and metaventral process and abdominal ventrites are also informative to distinguish the new species from remaining described Hemiosus. Diagnoses, illustrations and habitat characteristics are provided.